2017
DOI: 10.1063/1674-0068/30/cjcp1703031
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation on 1,3-Butadiene/Propyne Co-pyrolysis and Insight into Synergistic Effect on Aromatic Hydrocarbon Formation

Abstract: A numerical investigation on the co-pyrolysis of 1,3-butadiene and propyne is performed to explore the synergistic effect between fuel components on aromatic hydrocarbon formation. A detailed kinetic model of 1,3-butadiene/propyne co-pyrolysis with the sub-mechanism of aromatic hydrocarbon formation is developed and validated on previous 1,3-butadiene and propyne pyrolysis experiments. The model is able to reproduce both the single component pyrolysis and the co-pyrolysis experiments, as well as the synergisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…To quantitatively explain the formation of the identified products, we incorporate a reaction kinetic model into the SiC microreactor to rationalize the experimentally derived branching ratios of the reaction products at 1400 K. The model is based on the 1,3-butadiene pyrolysis model of Li et al 42 and we incorporate the detailed C 3 H 3 Br pyrolysis reaction pathways into the model and add the unimolecular isomerization and hydrogen-assisted reactions (R18–R20 in Fig. 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To quantitatively explain the formation of the identified products, we incorporate a reaction kinetic model into the SiC microreactor to rationalize the experimentally derived branching ratios of the reaction products at 1400 K. The model is based on the 1,3-butadiene pyrolysis model of Li et al 42 and we incorporate the detailed C 3 H 3 Br pyrolysis reaction pathways into the model and add the unimolecular isomerization and hydrogen-assisted reactions (R18–R20 in Fig. 6).…”
Section: Resultsmentioning
confidence: 99%
“…The initial mole fractions of the C 3 H 3 Br, C 4 H 6 , and Helium are also calculated from the practical experiments. The chemical models were based on the 1,3-butadiene pyrolysis model of Li et al 42 by including the detailed C 3 H 3 Br pyrolysis reaction pathways.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to 1-hexene flame, 44 fulvene is almost totally produced from the recombination of allyl and propargyl radicals (R23), while the self-combination of propargyl radical (R24) only has minor contributions in 1-pentene pyrolysis. For toluene formation, both of the work of Li et al 45 and Podder et al 46 found that the yield of toluene in the copyrolysis of 1,3-butadiene and propyne is much higher than those in pyrolysis of single components, revealing the importance of synergistic effect on toluene formation through the recombination reaction between 1,3-butadiene and propargyl radical (R25). Toluene formation in 1-pentene pyrolysis is similar to the situation in copyrolysis of 1,3-butadiene and propyne 45,46 due to the abundant formation of 1,3-butadiene and propargyl radical.…”
Section: H 9 1 − 3 (+M) = C 4 H 6 + Ch 3 (+M) (R17)mentioning
confidence: 99%
“…For toluene formation, both of the work of Li et al 45 and Podder et al 46 found that the yield of toluene in the copyrolysis of 1,3-butadiene and propyne is much higher than those in pyrolysis of single components, revealing the importance of synergistic effect on toluene formation through the recombination reaction between 1,3-butadiene and propargyl radical (R25). Toluene formation in 1-pentene pyrolysis is similar to the situation in copyrolysis of 1,3-butadiene and propyne 45,46 due to the abundant formation of 1,3-butadiene and propargyl radical. It should be noted that the present model not incorporating R25 will make the simulated maximum mole fraction of toluene about one order of magnitude lower than the experimental results, which indicates the significant promoting effect of R25 on toluene formation in 1-pentene pyrolysis.…”
Section: H 9 1 − 3 (+M) = C 4 H 6 + Ch 3 (+M) (R17)mentioning
confidence: 99%